THE ROLE OF EDUCATIONAL ANIMATION IN INTERACTIVE LEARNING IN THE DIGITAL ERA - Widia Nopita (CV Grasta Glory, 2026)
The development of digital technology has encouraged changes in the learning process, particularly in the use of more innovative and interactive learning media. One of the rapidly growing media is educational animation, as it is able to present learning materials in a visual, dynamic, and engaging manner. This article aims to examine the role of educational animation in supporting interactive learning in digital era through a literute review method based on various relevant journals and scientific sources. The result of the study indicate that educational animation can increase student’s learning motivation, help them understand abstract concepts, and enhance student engagement in the learning process. In addition, educational animation also supports independent learning and accommodates various learning styles of student. Compared to conventional learning media, educational animation is considered more effective in improving conceptual understanding. Therefore, the development and utilization of educational animation need to be continuously improved to support more effective learning in the digital era.